An algorithmic approach to identifying the aetiology of acute encephalitis syndrome in India: results of a 4-year enhanced surveillance study. Issue 5 (May 2022) - Ravi, Vasanthapuram; Hameed, Shafeeq K Shahul; Desai, Anita; Mani, Reeta Subramanian; Reddy, Vijayalakshmi; Velayudhan, Anoop; Yadav, Ravi; Jain, Amita; Saikia, Lahari; Borthakur, A K; Sharma, Ajanta; Mohan, Daiji Gogoi; et al.
Summary: Background: Annual outbreaks of acute encephalitis syndrome pose a major health burden in India. Although Japanese encephalitis virus (JEV) accounts for around 15% of reported cases, the aetiology of most cases remains unknown. We aimed to establish an enhanced surveillance network and to use a standardised diagnostic algorithm to conduct a systematic evaluation of acute encephalitis syndrome in India. Methods: In this large-scale, systematic surveillance study in India, patients presenting with acute encephalitis syndrome (ie, acute onset of fever with altered mental status, seizure, or both) to any of the 18 participating hospitals across Uttar Pradesh, West Bengal, and Assam were evaluated for JEV (serum and cerebrospinal fluid [CSF] IgM ELISA) per standard of care. In enhanced surveillance, JEV IgM-negative specimens were additionally evaluated for scrub typhus, dengue virus, and West Nile virus by serum IgM ELISA, and for Streptococcus pneumoniae, Haemophilus influenzae, Neisseria meningitidis, dengue virus, herpes simplex virus, and enterovirus by CSF PCR across five referral laboratories. In 2017, chikungunya and Leptospira serum IgM by ELISA and Zika virus serum and CSF by PCR were also tested. Findings: Of 10 107 patients with acute encephalitis syndrome enrolled in enhanced surveillance between Jan 1, 2014, and Dec 31, 2017, 5734 (57·8%) of 9917 participants with available data were male and 6179 (62·7%) of 9856 were children aged 15 years and younger. Among patients who provided a sample of either CSF or serum in enhanced surveillance, an aetiology was identified in 1921 (33·2%) of 5786 patients enrolled between 2014 and 2016 and in 1484 (34·3%) of 4321 patients enrolled in 2017. The most commonly identified aetiologies were JEV (1023 [17·7%] of 5786 patients), scrub typhus (645 [18·5%] of 3489), and dengue virus (161 [5·2%] of 3124). Among participants who provided both CSF and serum specimens, an aetiology was identified in 1446 (38·3%) of 3774 patients enrolled between 2014 and 2016 and in 936 (40·3%) of 2324 enrolled in 2017, representing a 3·1-times increase in the number of patients with acute encephalitis syndrome with an identified aetiology compared with standard care alone (299 [12·9%]; p<0·0001). Interpretation: Implementation of a systematic diagnostic algorithm in an enhanced surveillance platform resulted in a 3·1-times increase in identification of the aetiology of acute encephalitis syndrome, besides JEV alone, and highlighted the importance of scrub typhus and dengue virus as important infectious aetiologies in India. These findings have prompted revision of the national testing guidelines for this syndrome across India. Funding: US Centers for Disease Control and Prevention.